Reflective functioning in mothers with addictions: Differential relationships involving family history of mental illness and substance use - Lowell, Amanda F.; Yatziv, Tal; Peacock-Chambers, Elizabeth; Zayde, Amanda; DeCoste, Cindy; Suchman, Nancy; McMahon, Thomas J. (Frontiers in Psychology, 2022)
Parental reflective functioning (RF) is often cited as an important domain in which mothers with addictions struggle in their roles as parents, though the links between addiction and RF remain unclear. Exposure to attachment trauma associated with parental mental illness and substance use is commonly associated with both addiction and lower RF. We thus examined how family history of parental mental illness and substance use may relate to the RF of mothers with addictions. One hundred ninety-four mothers in outpatient substance use treatment completed the Parent Development Interview and provided information about whether their mothers and fathers experienced mental illness or problems with substance use. Univariate ANOVAs revealed an interaction between family history of maternal mental illness and maternal substance use. Among mothers with a history of maternal substance use, those with a history of maternal mental illness had higher RF than those who had no history of maternal mental illness. Among mothers who did not report a family history of maternal mental illness, mothers who had a family history of maternal substance use exhibited significantly lower RF than mothers with no family history of maternal substance use. Exposure to paternal mental illness or substance use was not associated with mothers’ RF. These findings highlight the importance of disentangling the contributions of attachment trauma to mothers’ RF and utilizing interventions that support mothers’ capacity to reflect about how their early experiences of being cared for by a mother with a mental illness or addiction may impact their current caregiving behaviors.